PREVALENCE AND DETERMINANTS OF HYSTERECTOMY IN THE GYNECOLOGY UNIT OF AYUB TEACHING HOSPITAL, ABBOTTABAD - SHAHEEN, A; IQBAL, H; BIBI, I; HAYAT, A; SHAHID, S; WAZIR, SK (Biological and Clinical Sciences Research Journal, 2024)
Hysterectomy is one of the most common obstetric surgery performed on women. It provides symptomatic relief, reduces morbidity and enhances the quality of life but can also lead to complications like mental stress, infertility, fractures and cardiovascular insults. To the best of our knowledge, no studies have provided information regarding the prevalence and risk factors of hysterectomies in Pakistani females. Objective: The goal of this study is to investigate the prevalence and socio-demographic determinants of hysterectomy in a teaching hospital in Pakistan, Methods: This descriptive cross-sectional study was done in the Gynecology C unit of Ayub Teaching Hospital, Abbottabad from 25th July 2024 to 10th Oct, 2024 after taking approval from ethical committee. 246 patients who underwent major gynaecological procedures were included in this study. Basic demographics, type of procedure and indication for hysterectomy were noted after obtaining consent from the patient. Results: The overall prevalence of hysterectomy was around 36.9% in our study. Heavy menstrual bleeding (43.95%) was found to be the leading cause of hysterectomy followed by fibroid uterus and adenomyosis in 25.27% and 16.48% cases respectively. Additionally, age group 45-49 (OR: 1.04, 95% CI: 0.5-2.1), urban residence (OR: 1.08, 95% CI: 0.64-1.8), more gravida (OR: 2.08, 95% CI: 0.88-4.92) and higher socioeconomic levels (OR: 1.28, 95% CI: 0.62-2.64) were found to increase odds of hysterectomy, whereas having a job (OR: 0.83, 95% CI: 0.47-1.44) and getting college education (OR: 0.83, 95% CI: 0.4- 1.7) were found to decrease the risk of hysterectomy. Conclusion: The prevalence of hysterectomy was found to be higher than in other countries. Urban residence, multigravida, higher socioeconomic levels and older age groups tend to increase the odds of hysterectomy.